DETECTION OF SBEM-MRNA IN PERIPHERAL BLOOD OF PATIENTS WITH BREAST CANCER AND ITS CLINICAL SIGNIFICANCE - 杨华伟 杨南武 曹骥 刘剑仑 张传珉 陈建思 蒋奕 欧超 苏建家 (Chinese journal of cancer research, 2006)
Objective： The aim of the present study is to explore the expression of a specific marker of breast cancer, small breast epithefial mucin （SBEM） mRNA, in peripheral blood and to investigate its significance. Methods： The expressions of SBEM-mRNA in peripheral blood of 67 patients with breast cancer, 16 patients with benign breast disease, and 20 normal healthy volunteers were detected with nested reverse transcription-polymerase chain reaction （Nested-RT-PCR）. Results： SBEMomRNA was negative in healthy individuals and patients with benign breast tumor, but 50.7%（34/67） of breast cancer patients showed positive expression of SBEM-mRNA in peripheral blood, of whom 25%（2/8） were in stage Ⅰ, 45.8%（11/24） in stage Ⅱ, 43.75%（11/24） in stage Ⅲ and 73.7（14/19） in stage Ⅳ. The positive rate in stage Ⅳ was higher than that in stage Ⅰ, Ⅱ, Ⅲ （P〈0.05）. Expressions of SBEM-mRNA had no correlation with age, carcinoma size, pathological type, ER and PR state （P〉0.05）. Concision： SBEM-mRNA is specifically expressed in breast cancer and it may act as a marker for the detection of of breast cancer.